Enterovirus 71, One Virus and Many Stories - Shih-Min Wang; Tzong-Shiann Ho; Ching-Fen Shen; Ching-Chuan Liu (Elsevier, 2008)
Enterovirus 71 (EV71) has emerged as a significant cause of brainstem encephalitis and acute flaccid paralysis in Taiwan. It may be complicated by autonomic nervous system dysregulation and pulmonary edema (PE). Cytokines in the central nervous system and systemic inflammatory responses play important roles in the pathogenesis of EV71-associated PE. Pathogenesis-based management with intravenous immunoglobulin and milrinone has been associated with reduced mortality in children with severe EV71 infections.